3+-1x=-4

Simple and best practice solution for 3+-1x=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+-1x=-4 equation:



3+-1x=-4
We move all terms to the left:
3+-1x-(-4)=0
We add all the numbers together, and all the variables
-1x+7=0
We move all terms containing x to the left, all other terms to the right
-x=-7
x=-7/-1
x=+7

You can always share this solution

See similar equations:

| (5-3n)=4 | | (2x)+58=180 | | (?11/6)+m=-2/9? | | 3.5g+7=1.5g+15= | | -13=20m+5-2m | | 5x-1+15x+1=25x-25 | | 6.68=??2.3c+0.72.3c+0.7 | | -13=22m | | 3y+4=6y-+19 | | -3(b-15)=12b+30 | | 15y-23=6y+3 | | 225=a2 | | {2x-1}{3}=-5=-5 | | d=65+10 | | 2x-6+5x+3=13x-21 | | 10x+9+8x-9=180 | | (3x+96)°=180 | | 4x+11=77 | | ?2x-6=3x-21 | | 15y-23=6y+3+5y+6 | | (9x+204)°=180 | | {2x-1}{3}=-5 | | 55=2.5r+15 | | (3x+96)°=180(9x+204)°=180 | | 4x+452x-3=90 | | 18-10y=-2(1+5y) | | 13x-55=8x | | 4x-452x+3=90 | | 4x-452x-3=90 | | ?8(6x+5)=???48x?40?48x?40 | | 4(x-2)=6(2x+5) | | v+9/3=-3 |

Equations solver categories